2016
DOI: 10.1111/jre.12368
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and oxidative stress in patients with different periodontal status: a case–control study

Abstract: Obesity may influence periodontal tissue destruction and disease severity by increasing the level of oxidative stress in the presence of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 50 publications
7
44
0
3
Order By: Relevance
“…Oxidative stress in HFD-fed rats was presented as higher plasma ROS and lower plasma antioxidant levels in accordance with previous studies [13,14]. In the present study, the results indicated that OP and OR rats showed different degrees of oxidative damage.…”
Section: Discussionsupporting
confidence: 92%
“…Oxidative stress in HFD-fed rats was presented as higher plasma ROS and lower plasma antioxidant levels in accordance with previous studies [13,14]. In the present study, the results indicated that OP and OR rats showed different degrees of oxidative damage.…”
Section: Discussionsupporting
confidence: 92%
“…Present study showed significant positive correlations between MDA (serum and salivary) with weight and body mass index. Similar findings were observed by Atabay et al 18 indicating that increases in serum and salivary MDA levels associated with increased weight and BMI, regardless of periodontal status, are reflective of increases in oxidative stress as a result of obesity. Obesity may be described as a state in which systemic, low-grade inflammatory stimulus can produce oxidative stress 18 .…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were observed by Atabay et al 18 indicating that increases in serum and salivary MDA levels associated with increased weight and BMI, regardless of periodontal status, are reflective of increases in oxidative stress as a result of obesity. Obesity may be described as a state in which systemic, low-grade inflammatory stimulus can produce oxidative stress 18 . In contrast to our findings Blok et al 13 found that body mass index is not associated with MDA.…”
Section: Discussionsupporting
confidence: 87%
“…When polyunsaturated lipids undergo a series of non-enzymatic reactions that produce a wide range of intermediate and end products due to ROS, MDA was the most specific molecule and the one most often used for the measurement of biological lipid oxidation [20]. MDA in serum, saliva, or gingival crevicular fluid is a marker of oxidative stress in human chronic periodontitis [21,22,23]. In experimental periodontitis, an increased MDA level was observed in the periodontal tissue [24].…”
Section: Discussionmentioning
confidence: 99%